2011
DOI: 10.1042/cs20100425
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors in ocular surface diseases: overview and new findings

Abstract: The ocular surface is the first line of defence in the eye against environmental microbes. The ocular innate immune system consists of a combination of anatomical, mechanical and immunological defence mechanisms. TLRs (Toll-like receptors), widely expressed by the ocular surface, are able to recognize microbial pathogens and to trigger the earliest immune response leading to inflammation. Increasing evidence highlights the crucial role of TLRs in regulating innate immune responses during ocular surface infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 84 publications
(115 reference statements)
0
41
0
Order By: Relevance
“…Studies have demonstrated that Acanthamoeba trophozoites can activate TLR4 expressed on corneal epithelial cells, inducing proinflammatory cytokines and chemokines at the ocular surface (10,32). The activation of TLRs at the ocular surface by Acanthamoeba and the release of cytokines and chemokines can be the triggering events for the recruitment of innate immune cells, such as macrophages and neutrophils (33).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that Acanthamoeba trophozoites can activate TLR4 expressed on corneal epithelial cells, inducing proinflammatory cytokines and chemokines at the ocular surface (10,32). The activation of TLRs at the ocular surface by Acanthamoeba and the release of cytokines and chemokines can be the triggering events for the recruitment of innate immune cells, such as macrophages and neutrophils (33).…”
Section: Discussionmentioning
confidence: 99%
“…The cornea is the major refractive element of the adult eye, and consists of three layers, including a thick middle layer known as the stroma, separated by basement membranes from an external stratified epithelium and an inner layer of endothelial cells. The corneal epithelium is the interface with the environment and represents an active barrier against pathogens, commensal bacteria, toxic stimuli, and allergens (Lambiase et al, 2011). Due to the constant physical disruption of blinking and tear flow, in addition to the presence of antibacterial components, the ocular surface of healthy individuals inherently supports a small population of bacteria (Graham et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…TLRs are expressed in ocular surface, retinal, iris, and corneal epithelial cells [26][28]. In the context of intraocular infections, TLRs have been found to be important in inflammation in S. aureus [29] and B. cereus [30] endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%